THE NATURE OF CONCEPTOLOGY IN UZBEK LINGUISTICS: THEORETICAL FOUNDATIONS AND CURRENT PERSPECTIVES - Gaddin A.Y. (International Journal of Literature and Language Studies, 2024)
this article explores the nature and development of conceptology within Uzbek linguistics, examining its core theoretical principles, foundational scholars, and the unique features that shape conceptual studies in the Uzbek language environment. The paper compares broader global perspectives of conceptology with distinctive characteristics found in Uzbek linguistics, focusing on linguistic, cultural, and cognitive dimensions.